1987
DOI: 10.1055/s-0038-1646056
|View full text |Cite
|
Sign up to set email alerts
|

Shortening of Bleeding Time by 1-Deamino-8-Arginine Vasopressin (DDAVP) in the Absence of Platelet von Willebrand Factor in Gray Platelet Syndrome

Abstract: SummaryThe Gray platelet syndrome is a rare disorder characterised by the absence of platelet a-granules and their contents. We describe a new patient and the effects of infusions of l-deainino-8-aiginine vasopressin (DDAVP). The patient had a prolonged skin bleeding time and his platelets had reduced numbers of a-granules, increased vacuolation and reduced retention on glass beads. Flatelet von Willebrand factor antigen (vWf:Ag) was undetectable and levels of platelet fibrinogen, p-thioniboglobulin, platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The vWF:Ag concentration in plasma is still increased after 8 h in contrast to the platelet adhesiveness, which is back to baseline after about 3 h. As the relative proportion of large vWF multimers does not change during the ®rst 8 h after desmopressin, we do not believe that the platelet stimulation can be explained by the release of unusually large vWF multimers. Pfueller et al [21] found that prominent satellite bands appeared in the middle to low molecular weight multimer region of the vWF, but they could not explain the signi®cance of these bands. We made a similar observation in this study, but it is not probable that these bands have any importance for platelet function.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The vWF:Ag concentration in plasma is still increased after 8 h in contrast to the platelet adhesiveness, which is back to baseline after about 3 h. As the relative proportion of large vWF multimers does not change during the ®rst 8 h after desmopressin, we do not believe that the platelet stimulation can be explained by the release of unusually large vWF multimers. Pfueller et al [21] found that prominent satellite bands appeared in the middle to low molecular weight multimer region of the vWF, but they could not explain the signi®cance of these bands. We made a similar observation in this study, but it is not probable that these bands have any importance for platelet function.…”
Section: Discussionmentioning
confidence: 96%
“…Pfueller et al . [ 21] found that prominent satellite bands appeared in the middle to low molecular weight multimer region of the vWF, but they could not explain the significance of these bands. We made a similar observation in this study, but it is not probable that these bands have any importance for platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the data from these case series and from other numerous smaller series and case reports [6,21,23,36,45,[51][52][53][54][55][56][57][58][59][60][61][62], inherited disorders of platelet function that usually respond with a shortening of BT after DDAVP administration include defects of secretion (in particular other than d-storage pool deficiency) and of signal transduction and the May-Hegglin anomaly; an effect has been variably reported in Bernard-Soulier syndrome and rarely shown in GlanzmannÕs thrombasthenia and cyclo-oxygenase deficiency ( Table 3). The response may be broadly predicted by the BT at baseline, perhaps indicating that desmopressin is less useful in more severe platelet function abnormalities showing longer BT.…”
Section: Clinical Evidence Of Ddavp In Inherited Disorders Of Platelementioning
confidence: 99%
“…More recently, one family with an autosomal-dominant form of GPS associated with a dominant-negative GFI1B mutation was described [9]. Different abnormalities of platelet hemostatic functiondefective response to thrombin [10][11][12][13][14] and collagen [10][11][12][14][15][16][17][18], variable response to ADP and ristocetin [10-12, 14, 17, 18] and normal response to arachidonic acid [10,11,14] -have been described so far in GPS patients. In one case, a specific defect of GPVI associated with abnormal response to collagen and convulxin was described [17].…”
Section: Introductionmentioning
confidence: 98%